Outcomes of epilepsy surgery: Initial experiences in Chiang Mai - Jetjumnong, Chumpon (Biomedical Sciences and Clinical Medicine, 2018)
Objectives To report our initial experiences using surgical intervention to treat drug resistant epilepsy (DRE). Methods A retrospective review of DRE patients operated at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai University from 2014 to 2016 was conducted including evaluation of clinical data, surgical outcomes, and complications. Results Eight patients were operated during the study period, 6 males (75%) and 2 females (25%). The mean age at surgery was 15 years. Most were evaluated as DRE following unsuccessful treatment with a combination of three antiepileptic drugs. After surgery, five patients (62.5%) were free of disabling seizures (Engel class I), and three (37.5%) were almost seizure free (Engel class II). There was only one serious operative complication (memory disturbance) in one patient who underwent an anterior temporal lobectomy. Conclusion Our initial experience in epilepsy surgery for DRE has shown promising results. A comprehensive epilepsy surgery program should be established including improvement of the associated infrastructure and surgical expertise for the bene fits of patients